Data-Driven Opportunities from an Account-Based Fare Payment System. Issue 8 (December 2018) - Chan, Raymond; Vaishnav, Maulik; Wainwright, Scott; Murray, Paul; Cui, Alex
The development of an account-based transit card has provided an opportunity for the Chicago Transit Authority (CTA) to examine transit usage differently. This new automated fare card/smart card system integrates many parts of a transit fare system, such as physical card, fare product, purchase information, and transit use location. The data are also integrated on a much longer timeframe than the previous generation transit card system. Increased data longevity allows the CTA to embark on a longitudinal study of transit card usage by separating cards in a priori groups. In a period between May 2016 and May 2017, a slight decrease in cards used in the system led to a small ridership drop, but a larger drop in ridership was found in passengers who used the system from one year to the next. This longitudinal application of passenger utilization of the transit network provides the agency with additional information that can be used to adjust fare policies and start marketing campaigns based on customer usages. This allows the agency to improve decision-making ability with greater insight on customer behavior.